DIALOGUE IN A FOREIGN LANGUAGE LESSON AS A WAY TO REALIZATION PERSONAL AND DEVELOPMENTAL EDUCATION - О.І. Kopitsa (Academy of Cognitive and Natural Sciences, 2004)
In this article forming of dialogue culture among students is considered, and solving of the problem is in group activity of pupils at the foreign language lesson.